Health services use by children identified as heterozygous hemoglobinopathy mutation carriers via newborn screening - Khangura, Sara D.; Potter, Beth K.; Davies, Christine; Ducharme, Robin; Bota, A. B.; Hawken, Steven; Wilson, Kumanan; Karaceper, Maria D.; Klaassen, Robert J.; Little, Julian; Simpson, Ewurabena; Chakraborty, Pranesh (Université d'Ottawa | University of Ottawa, 2021)
Abstract Background Newborn screening (NBS) for sickle cell disease incidentally identifies heterozygous carriers of hemoglobinopathy mutations. In Ontario, Canada, these carrier results are not routinely disclosed, presenting an opportunity to investigate the potential health implications of carrier status. We aimed to compare rates of health services use among children identified as carriers of hemoglobinopathy mutations and those who received negative NBS results. Methods Eligible children underwent NBS in Ontario from October 2006 to March 2010 and were identified as carriers or as screen-negative controls, matched to carriers 5:1 based on neighbourhood and timing of birth. We used health care administrative data to determine frequencies of inpatient hospitalizations, emergency department (ED) visits, and physician encounters through March 2012, using multivariable negative binomial regression to compare rates of service use in the two cohorts. We analyzed data from 4987 carriers and 24,935 controls. Results Adjusted incidence rate ratios (95% CI) for service use in carriers versus controls among children < 1 year of age were: 1.11 (1.06–1.17) for ED visits; 0.97 (0.89–1.06) for inpatient hospitalization; and 1.02 (1.00–1.04) for physician encounters. Among children ≥1 year of age, adjusted rate ratios were: 1.03 (0.98–1.07) for ED visits; 1.14 (1.03–1.25) for inpatient hospitalization and 0.92 (0.90–0.94) for physician encounters. Conclusions While we identified statistically significant differences in health services use among carriers of hemoglobinopathy mutations relative to controls, effect sizes were small and directions of association inconsistent across age groups and health service types. Our findings are consistent with the assumption that carrier status is likely benign in early childhood.